An Anxiety in Learning English of Thai Students at Yala Rajabhat University (YRU) - Nur Ainee Samoh; M. Sofian Hadi (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The research problem formulated for this study is to examine the anxiety experienced by students when learning English and how they cope with it. Qualitative research is employed to collect data and focus on the research problem. The descriptive analysis is applied to provide answers to the questionnaire about Foreign Language Anxiety (FLA) factors of male and female students. The findings showed that foreign language anxiety of the first-year students at Yala Rajabhat University, Thailand, reached the same extent as that at different school levels. The current study shows that there is no discernible difference in the foreign language anxiety scale between male and female students.